Determining Dental Utilization Rates for Children: An Analysis of Data from the Iowa Medicaid and SCHIP Programs - Peter Damiano, DDS, MPH; Elizabeth T. Momany, PhD; James J. Crall, DDS, ScD (Blackwell Synergy, 2006)
Accessing dental care is a significant problem for children in Medicaid and SCHIP Evaluating the extent of the access problem is affected by the differential dental utilization rates as calculated by unique approaches used by national organizations.